(untitled) (Annals of Medical Research, 2021)
Aim: Hallux rigidus is osteoarthritis of the big toe and is a clinical tableau with progressive pain and movement loss. This study aims to present the clinical outcomes of patients with grade 3 and 4 hallux rigidus unresponsive to conservative treatment who had arthroplasty with two different metallic implants or arthrodesis and to compare the outcomes of these treatments.Material and Method: Forty patients with arthroplasty or arthrodesis surgery due to hallux rigidus performed by a single surgeon from 2013 to 2018 were retrospectively compared in terms of AOFAS, VAS and ROM measurements and functional scores.Results: When the clinical outcomes of patients with arthroplasty are compared, there was no statistically significant difference observed. When the arthrodesis group is compared with the arthroplasty groups, separately and combined, there was no statistically significant differences observed in terms of functional scores.Conclusion: Total joint arthroplasty performed on the big toe offers patients the possibility of a painless metatarsalphalangeal joint (MTPJ) without movement limitations or high complication rates. Arthrodesis is still the most reliable surgical salvage procedure; however, it should be chosen for use as a salvage procedure for stage hallux rigidus that is advanced in terms of function, as with other joints in the musculoskeletal system.Keywords: Arthroplasty; hallux rigidus; metatarsophalangeal joint; surgical treatment; joint functions.